2017
DOI: 10.1530/joe-16-0488
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-143 mediates the proliferative signaling pathway of FSH and regulates estradiol production

Abstract: MicroRNAs (MiRNAs) play important regulatory roles in many cellular processes. MiR-143 is highly enriched in the mouse ovary, but its roles and underlying mechanisms are not well understood. In the current study, we show that miR-143 is located in granulosa cells of primary, secondary and antral follicles. To explore the specific functions of miR-143, we transfected miR-143 inhibitor into primary cultured granulosa cells to study the loss of function of miR-143 and the results showed that miR-143 silencing sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 38 publications
1
30
0
1
Order By: Relevance
“…Understanding the expression patterns of miRNAs during the different phases of reproductive cycle (luteal or follicular phase) of mammals such as cattle would provide a better insight about post-transcriptional gene regulation underlining follicular atresia and oocyte ovulation [31,32] or to identify miRNAs governing the production of steroid essential for the normal processes of folliculogenesis [35][36][37][38][39]. Nevertheless, aberrant expression of developmentally relevant miRNAs during critical period of the reproductive cycle could negatively affect follicular development resulting for anovulation or ovulation of infertile oocytes.…”
Section: The Role Of Cellular Mirnas In Follicular Development and Oomentioning
confidence: 99%
“…Understanding the expression patterns of miRNAs during the different phases of reproductive cycle (luteal or follicular phase) of mammals such as cattle would provide a better insight about post-transcriptional gene regulation underlining follicular atresia and oocyte ovulation [31,32] or to identify miRNAs governing the production of steroid essential for the normal processes of folliculogenesis [35][36][37][38][39]. Nevertheless, aberrant expression of developmentally relevant miRNAs during critical period of the reproductive cycle could negatively affect follicular development resulting for anovulation or ovulation of infertile oocytes.…”
Section: The Role Of Cellular Mirnas In Follicular Development and Oomentioning
confidence: 99%
“…The localization and functional impact in the ovary of the abundant miR-143 was also undertaken ( 51 ). This miRNA was highly expressed in granulosa cells where it appeared to regulate E2 production but not that of P4.…”
Section: Regulation Of Ovarian Cycling By Mirnamentioning
confidence: 99%
“…Increasing miRNAs are considered to be clinical biomarkers for atherosclerosis (Feinberg & Moore, ). Many recent studies have indicated that miRNAs can control a lot of fundamental biological processes (Rajman & Schratt, ; Zhang et al, ). For example, miR‐100 can inhibit chronic vascular inflammation by stimulating endothelial autophagy (Pankratz et al, ).…”
Section: Introductionmentioning
confidence: 99%